Evaluation of Dental Students’ Medical History Records on Hypertension and Diabetes Mellitus at The National University of Malaysia - Chong, Jun Ai; Adam, Fara Azwin; Ang, Yee; Hassan, Laila Azwa; Mavani, Hetal Ashvin Kumar; Rajandram, Rama Krsna (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: A thorough medical history ensures safe dental practice. A good medical history guides clinicians in risk stratification to avoid medical emergencies and improve preparedness to prevent patient morbidity and mortality. This clinical audit aims to analyse the medical history taken by the dental students in patients with hypertension and/or diabetes mellitus (DM) and subsequently, recommend improvements in history-taking components in the dental practice. Methods: Hundred and two patients’ folders from the Faculty of Dentistry were examined by two independent auditors using a validated history-taking evaluation form. Six components of the medical history were classified as good or bad practices. Sociodemographic factors and distribution of the American Society of Anesthesiologists (ASA status) were described. The level of completeness of medical history records with years of study was assessed using the Chi-square test. Results: None of the students met 100% of the components required in medical history taking. Year three undergraduates performed poorly in the completeness of diagnosis and control of the medical condition whereby none of them had a good level of practice. The completeness of records did not differ between years of study except for diagnosis (p=0.026), control (p<0.001) and updating medical history (p=0.009) whereby the postgraduates had the best practice. Conclusion: This study highlighted marked deficiencies in taking a thorough medical history. Adaptation of the European Medical Risk Related History (EMRRH) form is recommended to be implemented in dental schools.